Bagaimana Situasi Politik mempengaruhi Abnormal Return Saham Besar di Indonesia - Lufthia Sevriana; Erie Febrian (The Indonesia Capital Market Institute, 2021)
This study presents data on abnormal stock return movements with simple calculations. The result of deep analysis using event study method from major stocks in each sector, prove that There is negative response by the market to the student demonstration during the end of September 2019 that create abnormal return condition until it gets back to be normal in the middle of October. The sectors studied include the banking sector, construction, infrastructure, consumer needs, media, industrial materials, machinery, mining, and health care. Stock returns in Indonesia with inefficient market conditions are vulnerable to issues. Capital markets tend to be easily influenced by political and macroeconomic conditions, but even though the condition of return is abnormal, investors still have the potential to get favourable results. Keywords: Stock market, Market efficiency, Event study, Stock Price, Stock Returns